A Decomposition Method for Structured Linear and Non-Linear Programs - Grigoriadis, M.D.; Ritter, K. (University of Wisconsin-Madison Department of Computer Sciences, 1968)
A decomposition method for non-linear programming problems with structured linear constraints is described. The structure of the constraint matrix is assumed to be block diagonal with a few coupling constraints and/or variables. The method is further specialized for linear objective functions. An algorithm for performing post optimality analysis - ranging and parametric programming - for such structured linear programs is included. Some computational experience and results for the linear case are presented.